Design of and development a diamond fly-cutting system - Jarrett, James (Cranfield University, 2005)
This thesis presents a conceptual design, for a single point diamond fly-cutting system. This design is based on the performance of an existing, diamond facing lathe. The design requirements for a precision machine tool have been considered, and a deterministic design philosophy has been adopted. The error motions within the diamond facing lathe are considered as effects, generated by defined causes. These causes include geometric, kinematic and dynamic sources. Diamond turning and flycutting processes have been compared and consideration has been given to the process influences, including variations in; diamond tool geometries, cutting forces, rotational error motions and the process characteristics required for an optimal surface finish. A single point diamond facing lathe has been refurbished and the dynamic error motions of this machine tool have been analysed, using different techniques. The stiffness properties have also been investigated, which indicate how the performance of the machine tool has been affected over time and during the refurbishment process. The dynamic error motions have been used to generate a set of technical specifications, governing the design of the fly-cutting system. A design concept has been presented and optimised. This includes a fly-cutting head, with a quick release tool holder based on a kinematically located side locking clamp. A design concept for a dynamic workpiece holder has also been presented, which monitors the error motions of the machine tool and orientates the workpiece accordingly. A three pair flexure system has been simulated to orientate the workpiece. Consideration has been given to mounting the workpiece, feedback transducers and the design of the control system. This thesis has provided the initial steps in the design of a single point diamond flycutting system. A further stage of development work is required to complete a detailed design.
Keywords: Precision; Machine; Analysis; Error; Flexure